Shrauta bhumi - Athavale, R. S. (Indore : Printed at the State Press, 1909)
On "the locus of the earliest Aryan civilisation", in reference to Tilak's "Arctic Home in the Vedas". On "the locus of the earliest Aryan civilisation", in reference to Tilak's "Arctic Home in the Vedas". Mode of access: Internet.